Gamma-glutamyl transferase variability and the risk of hospitalisation for heart failure. Issue 14 (17th April 2020) - Hong, So-hyeon; Lee, Ji Sung; Kim, Jung A; Lee, You-Bin; Roh, Eun; Yu, Ji Hee; Kim, Nam Hoon; Yoo, Hye Jin; Seo, Ji A; Kim, Sin Gon; Kim, Nan Hee; Baik, Sei Hyun; et al.
Abstract : Objective: Gamma-glutamyl transferase (GGT) is associated with oxidative stress, inflammation, cardiovascular disease and mortality. Variability in metabolic parameters has recently emerged as an indicator of adverse health outcomes, including heart failure (HF). Methods: We investigated whether GGT variability was associated with the incidence of hospitalisation for heart failure (HHF) in a Korean population without previous HF, ischaemic heart disease or liver disease. This longitudinal cohort study analysed 119 201 individuals from the Korean National Health Insurance Service-National Health Screening Cohort. GGT variability was calculated as the coefficient of variation (CV), SD and variability independent of the mean (VIM). Results: During the 8.4 years of follow-up, 1387 cases of HHF (1.16%) developed. In the multivariable-adjusted model, the HR of HHF was 1.22 (95% CI 1.05 to 1.42) in the highest quartile of GGT variability compared with the lowest quartile, as assessed by CV after adjusting for confounding factors, including alcohol consumption and mean GGT levels. Consistent results were obtained using other indices of GGT variability such as SD (HR 1.37, 95% CI 1.16 to 1.62) and VIM (HR 1.29, 95% CI 1.11 to 1.50). In a subgroup analysis stratified by risk factor variables, although a similar relationship was observed, it was more prominent in individuals with dyslipidaemia. Conclusions: The results of the present study demonstrated that variability in GGT was independently associated with the incidence of HHF. These findings suggest that higher GGT variability may be useful as an indicator of future risk of HF.